Marketing and AI: Shaping the Future Together Proceedings of the 2024 AMS Annual Conference, Coral Gables, FL, USA, May 22–24 - Jeseo, Vincent; Parajuli, Jasmine (Developments in Marketing Science: Proceedings of the Academy of Marketing Science, 2024)
XX, 149 p. 15 illus., 10 illus. in color.